Deficient Mitochondrial Biogenesis in Il-2 Activated Nk Cells Correlates with Impaired Pgc1-Alpha Upregulation in Elderly Humans - Montoya-Kunsting, M; Cortez-San Martin, M; Mejías-Medina, S; Ibanez-Vega, J (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Immunosenescence has been described as age-associated changes in the immune function which are thought to be responsible for the increased morbidity with age. Human Natural Killer (NK) cells are a specialized heterogeneous subpopulation of lymphocytes involved in immune defense against tumor and microbial diseases. Interestingly, aging-related NK cell dysfunction is associated with features of aging such as tumor incidence, reduced vaccination efficacy, and short survival due to infection. It is known that NK cell effector functions are critically dependent on cytokines and metabolic activity. Our aim was to determine whether there is a difference in purified human NK cell function in response to high concentration of IL-2 between young and elder donors. Here, we report that the stimulation of human NK cells with IL-2 (2000 U/mL) enhance NK cell cytotoxic activity from both young and elderly donors. However, while NK cells from young people responded to IL-2 signaling by increasing mitochondrial mass and mitochondrial membrane potential, no increase in these mitochondrial functional parameters was seen in purified NK cells from elderly subjects. Moreover, as purified NK cells from the young exhibited an almost three-fold increase in PGC-1 alpha expression after IL-2 (2000 U/mL) stimulation, PGC-1 alpha expression was inhibited in purified NK cells from elders. Furthermore, this response upon PGC-1 alpha expression after IL-2 stimulation promoted an increase in ROS production in NK cells from elderly humans, while no increase in ROS production was observed in NK cells of young donors. Our data show that IL-2 stimulates NK cell effector function through a signaling pathway which involves a PGC-1 alpha-dependent mitochondrial function in young NK cells, however it seems that NK cells from older donors exhibit an altered IL-2 signaling which affects mitochondrial function associated with an increased production of ROS which could represent a feature of NK cell senescence.